Correlation of weight and volume of modified radical mastectomy specimen with ptosis of breast in patients of breast cancer - Bhawani Pathak; Rajender Kumar Karwasra (Clinical Surgical Oncology)
Background: Preoperative assessment of breast features is indispensable for both cosmetic and reconstructive breast surgical procedures. In this study we aim to investigate the effect of breast ptosis on breast volume estimation by various methods. Methods: Fifty patients of breast cancer planned for modified radical mastectomy were taken up. Preoperatively breast anthropometric measurement taken, grade of ptosis was noted and breast volume was calculated by anthropometry and mammography and intraopratively mastectomy specimen weight and volume was recorded. Breast volume calculated by mammography and anthropometry compared with mastectomy specimen volume and weight and correlation with ptosis was statistically analyzed. Results: Mastectomy specimen volume showed best agreement with mastectomy specimen weight (r ​= ​.993, <.001), followed by mammographic method (r ​= ​.985, P ​< ​.001), anthropometry by breast circumference in supine method (r ​= ​.982, P ​< ​.001), anthropometry by breast circumference in upright method (r ​= ​.979, P ​< ​.001) and anthropometry by breast radius and mammary projection method (r ​= ​.969, P ​< ​.001). Conclusion: Mammography is simple, cost effective and most accurate method for breast volume estimation followed by anthropometric breast volume calculation. As size of breast and grade of breast ptosis increases the accuracy of all methods of breast volume estimation decreases.